2007
DOI: 10.1002/j.2168-9830.2007.tb00941.x
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Study of the Index of Learning Styles©

Abstract: A study was conducted on the Felder-Soloman Index of Learning Styles © (ILS) to assess reliability, factor structure, and construct validity as well to determine whether changing its dichotomous response scale to a five-option response scale would improve reliability and validity. Data collected in this study had internal consistency reliability ranging from 0.55 to 0.77 across the four learning style scales of the ILS. Factor analysis revealed that multiple factors were present within three of the learning st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
183
3
29

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(223 citation statements)
references
References 7 publications
8
183
3
29
Order By: Relevance
“…Learning styles describe how individuals receive, perceive, process, and understand information. 1,3,4 These interactions with information are essential components of problemsolving, and thus, suggest that learning styles may be a valuable lens through which to evaluate our methods for developing students as problem solvers. We used the Felder-Silverman model specifically because of its historical application in engineering, and its multidimensional nature allowing for two preferences in each of four dimensions (active/reflective, sensing/intuitive, visual/verbal, sequential/global) with subsequent strengths (strong, moderate, balanced) for each preference.…”
Section: Overview Of the Work And Methodsmentioning
confidence: 99%
“…Learning styles describe how individuals receive, perceive, process, and understand information. 1,3,4 These interactions with information are essential components of problemsolving, and thus, suggest that learning styles may be a valuable lens through which to evaluate our methods for developing students as problem solvers. We used the Felder-Silverman model specifically because of its historical application in engineering, and its multidimensional nature allowing for two preferences in each of four dimensions (active/reflective, sensing/intuitive, visual/verbal, sequential/global) with subsequent strengths (strong, moderate, balanced) for each preference.…”
Section: Overview Of the Work And Methodsmentioning
confidence: 99%
“…between engineering students and biology students. Felder's assessment is popular among engineering education studies [21][22][23] . Students were also given a pre-laboratory quiz and instructional preferences survey.…”
Section: Methodsmentioning
confidence: 99%
“…These dimensions in the ILS draw from other well-known learning style models such as the Myers Briggs Type Indicator (MBTI) and the Kolb learning style index 27 . The ILS has a substantial history of use and has been proven to provide consistent and valid results in numerous evaluative studies [27][28][29][30][31] . Reliability tests yielded Cronbach alpha results greater than 0.5 and consistent in all the ILS scales; while Pearson's correlation and factor analysis tests conducted also indicated that the different dimensions were indeed distinct -with a mild association found between the sequential global and sensing initiative scales 26,29 .…”
Section: Introductionmentioning
confidence: 99%
“…The ILS has a substantial history of use and has been proven to provide consistent and valid results in numerous evaluative studies [27][28][29][30][31] . Reliability tests yielded Cronbach alpha results greater than 0.5 and consistent in all the ILS scales; while Pearson's correlation and factor analysis tests conducted also indicated that the different dimensions were indeed distinct -with a mild association found between the sequential global and sensing initiative scales 26,29 . Testing in various samples over time also showed support for the notion that the constructs being assessed by the ILS were valid 28,30,31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation